Pengaruh Dividen, Pertumbuhan Aset, dan Volume Perdagangan terhadap Volalitas Harga Saham JII70 - Muhammad Rifqi Harish; Siti Amaroh (Reviu Akuntansi, Manajemen, dan Bisnis, 2023)
Purpose: The study is intended to empirically examine the fundamental factors of micro companies in influencing stock price volatility in the Jakarta Islamic Index 70 From the period 2019-2023. The form of Islamic stock market reaction in the Jakarta Islamic Index 70 is shown by fluctuations resulting in stock price volatility events in the 2019-2020 period. Through this research, the fundamental factors taken, namely the distribution of company dividends, the growth of company assets, and the volume of stock trading in stocks in JII70 for the 2019-2020 period. Research Methodology: With data from the Indonesian stock exchange from 2019 to 2022, comparative descriptive approaches and quantitative methodologies were employed in this study. Purposive sampling was used to sample, and it revealed 18 businesses that fit the bill. Results: The findings results of the study, which was conducted on 18 companies listed on the Jakarta Islamic Index 70 during the 2019-2022 period, showed that stock price volatility was influenced by variable dividend payout ratios with a significant value of 0.048, stock trading volume was also influential with a significant value of 0.041, and was not influenced by asset growth variables. Limitation: Some scientific limitations in this study, that this analysis only includes 3 independent variables whose capacity to explain the dependent variable is still somewhat limited. The companies listed in the Jakarta Islamic Index are 70, producing a small research sample and the research period is still relatively short. Contribution: The results of this study will likely be applied in investment decision-making. Businesses with concerns about fluctuations, and stock price volatility can also utilize this research's findings as knowledge.